2019
DOI: 10.1101/509588
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Birth-and-death evolution of the fatty acyl-CoA reductase (FAR) gene family and diversification of cuticular hydrocarbon synthesis in Drosophila

Abstract: The birth-and-death evolutionary model proposes that some members of a multigene family are phylogenetically stable and persist as a single copy over time whereas other members are phylogenetically unstable and undergo frequent duplication and loss. Functional studies suggest that stable genes are likely to encode essential functions, while rapidly evolving genes reflect phenotypic differences in traits that diverge rapidly among species. One such class of rapidly diverging traits are insect cuticular hydrocar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…The layer of waxy cuticular hydrocarbons (CHCs), the outermost hydrophobic layer on the insect body surface, has an important role in controlling water loss by reducing the rate of evaporation through the cuticle. CHCs are synthesized in specialized oenocyte cells via the fatty acyl‐CoA synthesis pathway involving a series of fatty acyl‐CoA modification enzymes such as desaturases, elongases, and reductases that metabolize acetyl‐CoA to alcohols and aldehydes before the final decarbonylation to long‐chained hydrocarbons by a CYP4G cytochrome P450 enzyme . Removing all CHCs by RNA interference (RNAi) knockdown of this CYP4G ortholog in D. melanogaster , Cyp4g1 , resulted in severe desiccation sensitivity in D. melanogaster .…”
Section: Mechanisms Underlying How Climate Change Can Affect Insecticmentioning
confidence: 99%
“…The layer of waxy cuticular hydrocarbons (CHCs), the outermost hydrophobic layer on the insect body surface, has an important role in controlling water loss by reducing the rate of evaporation through the cuticle. CHCs are synthesized in specialized oenocyte cells via the fatty acyl‐CoA synthesis pathway involving a series of fatty acyl‐CoA modification enzymes such as desaturases, elongases, and reductases that metabolize acetyl‐CoA to alcohols and aldehydes before the final decarbonylation to long‐chained hydrocarbons by a CYP4G cytochrome P450 enzyme . Removing all CHCs by RNA interference (RNAi) knockdown of this CYP4G ortholog in D. melanogaster , Cyp4g1 , resulted in severe desiccation sensitivity in D. melanogaster .…”
Section: Mechanisms Underlying How Climate Change Can Affect Insecticmentioning
confidence: 99%
“…In D. melanogaster, 19 elo genes have been identified in total [21], but only five have been clearly associated with CHC biosynthesis and variation [56,58]. Concerning far genes, from 17 identified in the D. melanogster genome [59], two have a demonstrated impact on CHC biosynthesis [56]. This already indicates the difficulty in associating members of these two large and diverse gene families with CHC biosynthesis and variation.…”
Section: Discussionmentioning
confidence: 99%
“…Second, Nasonia CHC profiles appear to be more complex, generally containing more compound classes, including di-, tri-and tetra-methyl-branched alkanes, in contrast to CHC profiles of D. melanogaster (compare electronic supplementary material, tables S8 and S9). It has been demonstrated that the far gene family shows particularly high evolutionary turnover rates, which could allow, in turn, for a concordant rapid diversification of CHC profiles [59]. This also argues for the involvement of a larger set of far genes in CHC biosynthesis in Nasonia than in Drosophila due to the more diverse and complex nature of Nasonia CHC profiles.…”
Section: Discussionmentioning
confidence: 99%
“…The CHC biosynthesis pathway is largely conserved in insects and is made up of several fatty acyl-CoA synthesis gene families such as fatty acyl-CoA synthetases, desaturases, fatty acyl-CoA reductases (FARs), and elongases (Blomquist and Ginzel, 2021). These gene families evolved rapidly and contribute to the diversification of CHCs across insects (Finck et al, 2016;Finet et al, 2019;Helmkampf et al, 2015;Tupec et al, 2019). Gains and losses of these genes as well as changes in their oenocyte expression are likely to contribute to CHC changes and the evolution of desiccation resistance in different insect species.…”
Section: Lineage Specific Genetic Basis For the Evolution Of Desiccat...mentioning
confidence: 99%